Teater Tradisional Sebagai Dokumen Komunitas - Probonegoro-Kleden, Ninuk (P2KK LIPI, 2000)
Theoretical assumption which underlies this article is that theatre in general and traditional local theatre in particular can be treated as a social document of its supporting community. However, the process of documentation usually takes place only symbolically at various levels of signification. In the case of traditional theatres in Java it is very important to establish where to find out what is documented and how it is conveyed. In the case of Lenong theatre of Betawi community it is surprising that the political chaos in J 998 in Jakarta is hardly worked out except in very limited form in its dialog.